Breastfeeding beyond the big smoke: Who provides support for mothers in rural Western Australia? - Cox, K.; Giglia, Roslyn; Binns, Colin (Wiley-Blackwell Publishing Asia, 2017)
Introduction: Despite strong and growing evidence for the benefits of exclusive breastfeeding to 6 months of age, few infants in developed countries reach this milestone. Although breastfeeding practice and its determinants are well described for women in metropolitan areas, there is limited evidence for rural and regional areas of Australia. This paper describes the influence of advice and support on breastfeeding duration for women in rural areas of Western Australia in the first 6 months of their infants' lives. Methods: A cohort of 427 women and their infants were recruited from hospitals in regional Western Australia and followed up for a period of 12 months. Information about feeding methods was gathered in hospital and at a further seven follow-up contacts. Results: Women who had attended antenatal classes were less likely to have ceased exclusively breastfeeding before 6 months than those who had not attended classes (aHR: 0.61, 95% CI: 0.41-0.91). No significant associations were found between provision of information alone and duration of breastfeeding. Breastfeeding advice and support in the first 6 months was most commonly sought from Child Health Nurses, General Practitioners and friends. Conclusions: Antenatal group education is effective in supporting breastfeeding duration for rural women and should be a key priority for rural health service providers. Health professionals are common sources of breastfeeding support postnatally, however creating and maintaining positive and supportive social networks for mothers might also contribute to increasing the proportion of rural infants who meet the World Health Organization guidelines for exclusive breastfeeding.